2019
DOI: 10.7759/cureus.3933
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Multidetector Computed Tomography in Detection of Esophageal Varices

Abstract: ObjectiveTo determine the diagnostic accuracy of multidetector computed tomography (MDCT) in the detection of esophageal varices by taking endoscopy as the reference standard.Materials and methodsThis was a cross-sectional prospective study conducted at the Department of Radiology, Aga Khan University Hospital, (AKUH) Karachi, for the duration of 12 months from August 1, 2014 to July 31, 2015. One hundred ninety-six patients with a suspicion of chronic liver disease/cirrhosis undergoing 64 slice MDCT were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Salahshour et al [26] reported 63.49% sensitivity, 81.97% specificity, and 72.58% accuracy. Hassan et al [27] reported 98% sensitivity and 100% specificity. Deng et al [28] reported 95% sensitivity and 71% specificity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Salahshour et al [26] reported 63.49% sensitivity, 81.97% specificity, and 72.58% accuracy. Hassan et al [27] reported 98% sensitivity and 100% specificity. Deng et al [28] reported 95% sensitivity and 71% specificity.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies [26][27][28] assessed the accuracy of MDCT in the prediction of EVs with variable results. Salahshour et al [26] reported 63.49% sensitivity, 81.97% specificity, and 72.58% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, CT was found to have approximately 90% sensitivity and 50% specificity in detecting esophageal varices [14]. A recent retrospective study reported a CT sensitivity of 98.96%, specificity of 100%, and diagnostic accuracy of 98.97% for EV in patients with chronic liver disease [35]. Therefore, CT can be considered as a potential noninvasive, less expensive and more compliant EV detection method compared to the invasive endoscopic screening modality.…”
Section: Discussionmentioning
confidence: 99%
“…Multidetector CT (MDCT) has a predictive value of GEVs [76]. Hassan M et al showed MDCT displayed a diagnostic accuracy of 98.97% for EVs [77]. Contrast- enhanced CT scans displayed an AUROC of 0.835 for EV detection [78].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 99%